Enhancing media literacy skill building in pedagogical universities: Our view and experience - Buchatska, Svitlana; Zarichna, Olena; Matiienko, Olena; Khurtenko, Oksana (East European Journal of Psycholinguistics, 2024)
The article presents a review of the integration of media literacy content in foreign language courses at pedagogical higher education institutions. This study is aimed to share and present for academic discussion some of the authors’ perspectives that proved to be successful in mastering media literacy skills as well as in developing language competencies in EFL learners. A particular focus has been made on the methodological base, the principles and strategies of media literacy skill building as well as on the criteria for the selection of learning materials and techniques that ensure the effective implementation of media literacy programs into the existing syllabi. The use of contemporary teaching methods such as flipped classroom, problem-based learning, group projects, capitalizing on higher order thinking skills and interactive classroom activities is viewed as an integrated approach aimed to develop critical perception of media products alongside with a range of sociocultural and communicative competences in students of pedagogy. One of the main objectives of integrating media literacy content into a variety of tertiary courses is to enhance emotional resilience to manipulative influences of the media which is achieved through activating critical thinking skills referring to information flow as well as to students’ own media consumption habits. The pilot implementation being conducted in the terms of the international project “Learn to Discern”, preserved its original methodological constituents which included media literacy as such, information literacy, critical thinking, digital and visual literacy and fact checking skills. Acknowledgements The study is supported by the International Research and Exchanges Board (IREX), the Embassy of the United States of America and the Embassy of the United Kingdom in Ukraine, in partnership with the Ministry of Education and Science of Ukraine and the Ukrainian Press Academy. Disclosure Statement The authors reported no potential conflicts of interest. * Corresponding author: Svitlana Buchatska, 0000-0001-6063-5858 sbuchatska@vspu.edu.ua